DEVELOPMENT OF AUTO-GENERATING AERODYNAMIC LOADS FOR WING-BOX FINITE ELEMENT MODEL BASED ON SCHRENK METHOD - Zain, R; Pamungkas, I. R; Wafiqni, Wafiqni; Yusni, A (Mesin, 2009)
This paper describes the development of computer application for computing the wing lift distribution and auto-locating each sectional lift force to the appropriate nodes of wing-box finite element model (FEM). In Catia-V5 environment, Visual Basic .Net is intensively utilized to access several Catiaâs Component Object Models (COMs) by implementing several user interfaces for collecting flight data from user and for linking to the wing-box finite element model that already created in the previous work. The distribution of lift force is governed by Schrenk method, where the distribution is multiplied by limit load factor and safety factors in order to conform to the airworthiness requirement. The lift force is computed for each rib-space area and located on a point of quarter chord called a Handler. Correspondingly each upper wing surface of rib-space called Agent conducts as media to transform each lift force from a handler into their associated nodes of FEM. To demonstrate this work, a hypothetical N250 wing box structures is utilized for a case study. The result of this work is very useful to be utilized for wing design involving aerodynamic and structure analysis.